To find the y-value that corresponds to the x-value of -1 for the function \( f(x) = -2x^2 + 5x \), we need to substitute \(-1\) for \(x\) in the function.
Let's calculate it:
\[ f(-1) = -2(-1)^2 + 5(-1) \] \[ = -2(1) - 5 \] \[ = -2 - 5 \] \[ = -7 \]
So, the y-value that corresponds to \( x = -1 \) is \(-7\).
If you were to graph the function, it would be a downward-opening parabola with its vertex located above the x-axis, and at the point where \( x = -1 \), the function would yield a value of \(-7\).